Strange birds : a field guide to ruffling feathers - 1972- (Kokila, 2019)
How do strangers become friends? Ofelia Castillo is searching for a story. While her friends leave their boring Florida town for summer camps and family vacations, she braces for zero excitement. Lane Disanti would like her whole family to kick rocks. Especially her parents, who sent her to live with her grandmother for the summer while they finalize their divorce. Aster Douglas has one summer to figure out how to be a kid. She's been homeschooled by her grandfather her whole life, and it's easier for her